Morphological and Histological Study of an ‘Iliac Venous Ladder’ Associated with Very Short Common Iliac Arteries - Nayak, Satheesha B.; Surendran, Sudarshan; Nelluri, Venu Madhav; Shetty, Prakashchandra (Journal of Morphological Sciences, 2019)
Introduction Communications between iliac veins in the pelvis are reported to be rare occurrences, which are mostly due to developmental abnormalities. The common iliac vein is formed by the joining of the internal and external iliac veins. Here, we present a detailed morphological and histological study of a rare communication found between the internal and external iliac veins, which would prove to be of substantial value to the knowledge of vessels in the pelvis, both for clinicians and surgeons.Materials and Methods In the present study, we came across a rare communication in the form of a ladder, between the left internal and external iliac veins in a 70-year-old male cadaver. There were two communications (named upper and lower communications) between the external and internal iliac veins, before they joined to form the common iliac vein. On naked eye observation, the lumen of the right common iliac vein appeared to be wider than on the left side. The lengths of these communications and the distance between each of their attachments have been measured and tabulated. The walls of these veins, their microscopic sections and their communication involved in the case were taken. The possible causes for these variations were congenital, owing to the complicated nature of the developmental process involved in the formation of the inferior vena cava and the venous system of the lower limb.Results The structure of all the veins involved in this case and the communications were seen to be normal. The thickness of these walls were measured and tabulated for uniformity around the circumference of the wall of these veins. All the measurements from the structural variations and from the histological observations are tabulated in our results.Conclusion The complicated development sequence of these veins could have possibly led to the persistence of these communications. Such a developmental variation does not seem to pose any threat until unless encountered under clinical or surgical interventions, as the histological structure of the walls of the communications as well as the major channels connected appeared to be normal and well-developed. The detailed morphological and histological features of these structures involved in the variation along with the possible complications have been presented in the present report. Knowledge of these variations and complications due to injury plays a key role in a clinical setup.
Keywords: external iliac vein; internal iliac vein; histology; pelvis; inferior vena cava; iliac artery